2018
DOI: 10.1590/1678-6971/eramg180076
|View full text |Cite
|
Sign up to set email alerts
|

Leadership as Cultural Practice

Abstract: It is not allowed the use for commercial purposes. Este artigo pode ser copiado, distribuído, exibido, transmitido ou adaptado desde que citados, de forma clara e explícita, o nome da revista, a edição, o ano e as páginas nas quais o artigo foi publicado originalmente, mas sem sugerir que a RAM endosse a reutilização do artigo. Esse termo de licenciamento deve ser explicitado para os casos de reutilização ou distribuição para terceiros. Não é permitido o uso para fins comerciais. This is an open-access article… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 57 publications
(54 reference statements)
1
8
0
1
Order By: Relevance
“…It is instructive to note that values impact on attitudes which in turn inform behaviours and mostly values are context-driven. Socio-cultural elements are fundamental in orienting the construction of organisational and leadership practices by way of how leaders make decisions and how they act and interact (Vilas-Boas et al, 2018). With such inbuilt values, the respondent as a leader in an organisation is bringing such values to bear.…”
Section: Sense Making Of Constructive Organisational Leadershipmentioning
confidence: 99%
“…It is instructive to note that values impact on attitudes which in turn inform behaviours and mostly values are context-driven. Socio-cultural elements are fundamental in orienting the construction of organisational and leadership practices by way of how leaders make decisions and how they act and interact (Vilas-Boas et al, 2018). With such inbuilt values, the respondent as a leader in an organisation is bringing such values to bear.…”
Section: Sense Making Of Constructive Organisational Leadershipmentioning
confidence: 99%
“…Effective Leadership in the 21st Century: Lessons for the Tourism Sector in the African Continent DOI: http://dx.doi.org /10.5772/intechopen.93844 For example, destinations are reinventing themselves using socio-cultural assets to attract tourists. This has been a common practice, particularly in leadership, where cultural expression involves issues and conflicts connected to the leaders and followers inside a variety of international, national, regional and organisational contexts [56]. Figure 2 presents the African leadership concepts.…”
Section: African Leadership Concepts: Lessons For the Tourism Sectormentioning
confidence: 99%
“…Eyong (2017) noted the existence of marked difference in conception, power and roles arrangements and relationships, and practices of Afrocentric and Anglo-Saxon perspectives. Vilas-Boas et al (2018) indicated that leadership is culture based, collective and social phenomena. Similarly, Collinson and Tourish (2015) asserted that there is no single way to lead; study and teach leadership.…”
Section: Introductionmentioning
confidence: 99%
“…According to Mazama (2001), “our problems as African people are our usually unconscious adaption of western world view and their attendant conceptual framework” (Mazama, 2001, p. 387). Besides Afrocentrists; the critical leadership (Collinson, 2011; Collinson and Tourish, 2015), the cultural/anthropological leadership (Edwards, 2015; Jepson, 2009; Vilas-Boas et al, 2018) and the language leadership researchers (Jepson, 2010; Schedlitzki et al, 2017) are calling for considering contextual differences, discourses, and meanings making process differences. They have called for multiplicity and differences (Collinson, 2011, 2014; Eyong, 2017; Schedlitzki et al, 2017).…”
Section: Introductionmentioning
confidence: 99%